Occurrence of nitrosamines and their precursors in North American drinking waters. Issue 6 (1st December 2020) - Krasner, Stuart W.; Roback, Shannon; Qian, Yichao; Li, Xing‐Fang; Marfil‐Vega, Ruth; Bukhari, Zia
Abstract: Eight N‐ nitrosamines were measured at 37 water plants in the United States and Canada. Five tobacco‐specific nitrosamines (TSNAs) were measured in selected waters. N ‐Nitrosodimethylamine (NDMA) was preferentially formed in chloraminated systems (maximum detention time: median 4.4 ng/L). A small amount was detected in some chlorinated systems (90th percentile <2.0 ng/L). After ozone (before chloramines), NDMA was sometimes detected (90th percentile 2.9 ng/L), suggesting that the ozone did not react with precursors to form NDMA. The chloramine plants that temporarily switched to chlorine typically produced less NDMA (Plant 29 reduced NDMA formation, on average, from 34 to 4 ng). More NDMA was produced during spring runoff, when there were elevated levels of ammonia and NDMA precursors in the source water. More NDMA was formed when there were higher levels of poly(diallyldimethylammonium chloride) (polyDADMAC) used. N ‐Nitrosomorpholene was found to be a contaminant and not a disinfection byproduct; it did not increase during chloramination. TSNAs were produced during spring runoff; source water ammonia impacted the chlor(am)ine chemistry.